Eastern, central and western Hungary - variations of neolithisation models - Bánffy, Eszter (Documenta Praehistorica, 2006)
Until recent times, the Carpathian Basin was regarded as a uniform zone of neolithization. In the last few years it has become clear that at least three different types of transitions can be distinguished in the Eastern Plain (Alföld) region: one in the Jászság area with authentic Mesolithic sites, one in the northern, one in the northeastern fringes of the Körös distribution area, and a further one in the southern part of the Danube-Tisza Interfluve where the impact of the formative Vinča culture must also be reckoned with. All regions differ from each other, concerning the contacts with Mesolithic population and the phases of neolithisation. Regarding Transdanubia, the picture becomes even more complex. The transitionto the Neolithic obviously differed in each region: in the Drava valley where the Starčevo presence was very intensive, in the marshland aroundLake Balaton, in the Rába valley lying close to the Alpine foreland, inthe northern Transdanubian Danube valley and in the Little Hungarian Plain.Rejecting the simplifying model the assumption of a mosaic-like seriesof variations in the neolithisation process is offered. The process of Neolithisation is thus is far from being unified in the various regions. Thisshort study tries to seek different models of neolithisation behind the differences.
Keywords: Karpati; Kárpáti; Madžarska; Hungary; archaeology; arheologija; mezolitik; neolitik; kulturna zgodovina; družbeni razvoj; tranzicija